Polishing composition

By using a surface protecting agent of a cellulose derivative and a vinyl alcohol-based dispersant in the polishing composition, the problem of difficulty in reducing surface defects in the prior art is solved, and the effect of higher surface smoothness and fewer defects is achieved.

CN119432323APending Publication Date: 2025-02-14FUJIMI INCORPORATED
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411487856.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2016-11-22
Filing Date
2017-11-15
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing grinding compositions are difficult to effectively reduce surface defects in the fine grinding process, especially light spot defects that cannot be removed (LPD-N), and the quality of cellulose derivatives is unstable, which affects the dispersion and surface protection of the composition. Effect.

Method used

The abrasive composition is adopted that includes abrasive particles, alkaline compounds and surface protecting agents. The surface protecting agent is composed of cellulose derivatives and vinyl alcohol-based dispersant. The dispersion parameter α is less than 100. By optimizing cellulose derivatives and dispersions The molecular weight and content of the agent improve the dispersion and surface protection effect of the composition.

Benefits of technology

It effectively reduces the surface defects after grinding, especially the LPD-N number, improves the surface quality, and ensures the surface smoothness and performance of fewer defects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005099169960000281
    Figure BDA0005099169960000281
Patent Text Reader

Abstract

Provided is a polishing composition which has a composition containing a cellulose derivative and which is capable of effectively reducing surface defects after polishing. The present application provides a polishing composition comprising abrasive grains, a basic compound, and a surface protective agent. The surface protective agent contains a cellulose derivative and a vinyl alcohol dispersant. The dispersibility parameter alpha of the surface protective agent is lower than 100.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present application is a divisional application of an application filed on November 15, 2017, with application number 201780072039.6 and invention name “Polishing Composition”. Technical Field

[0002] The present invention relates to a polishing composition. This application claims priority based on Japanese Patent Application No. 2016-226666, filed on November 22, 2016, the entire contents of which are incorporated herein by reference. Background Art

[0003] For the surface of materials such as metals, semi-metals, non-metals, and oxides thereof, polishing using a polishing composition containing abrasive grains is implemented. For example, the surface of a silicon substrate used in the manufacture of semiconductor products is generally processed into a high-quality mirror surface through a lapping process and a polishing process. The above-mentioned polishing process typically includes a pre-polishing process and a fine polishing process (fine grinding process). As technical documents on the polishing composition mainly used for the purpose of grinding semiconductor substrates such as silicon wafers, Patent Documents 1 and 2 can be cited.

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Publication No. 2012-89862

[0007] Patent Document 2: Japanese Patent Application Publication No. 2015-124231 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] The polishing composition used in the finish polishing process is required to achieve the performance of a surface with low haze and few surface defects after polishing. The above-mentioned finish polishing process is a finish polishing process of a semiconductor substrate or other substrate such as a silicon wafer. Most of the polishing compositions used for this purpose contain abrasive grains and water, and also contain water-soluble polymers for the purpose of protecting the surface of the polishing object or improving wettability. Among them, hydroxyethyl cellulose (HEC) can be cited as a general-purpose water-soluble polymer.

[0010] However, cellulose derivatives represented by HEC use cellulose, which is a natural product, as a raw material, so the quality is likely to be uneven. Therefore, it is difficult to accurately suppress fine aggregation that may cause surface defects in polishing compositions containing cellulose derivatives. Although patent documents 1 and 2 record the technology of reducing surface defects in polishing compositions using HEC, even with this technology, it is still unable to fully respond to the situation that the degree of surface quality after polishing has been required in recent years.

[0011] Therefore, an object of the present invention is to provide a polishing composition comprising a cellulose derivative and capable of effectively reducing surface defects after polishing.

[0012] Solutions for solving problems

[0013] The polishing composition provided by the present specification comprises abrasive grains, an alkaline compound and a surface protective agent. The surface protective agent comprises a cellulose derivative and a vinyl alcohol-based dispersant. Here, the dispersibility parameter α of the surface protective agent is less than 100. With this polishing composition, the advantages obtained by using a cellulose derivative can be utilized, and the surface defects after polishing can be effectively reduced. The polishing composition can effectively reduce defects such as Light Point Defect Non-cleanable (LPD-N) that cannot be solved by polishing, washing, drying, etc.

[0014] The weight average molecular weight (Mw) of the cellulose derivative can be set to, for example, 5×10 4 Above and below 50×10 4 When the cellulose derivative has a Mw within the above range, the dispersibility parameter α can be suppressed, and the function of protecting the polishing object or improving wettability tends to be appropriately exerted.

[0015] The Mw of the vinyl alcohol-based dispersant may be, for example, 90% or less of the Mw of the cellulose derivative. With such a configuration, the effect of reducing the dispersibility parameter α obtained by using the vinyl alcohol-based dispersant tends to be more effectively exerted.

[0016] The content of the vinyl alcohol-based dispersant can be, for example, 0.1 g or more and 80 g or less relative to 100 g of the cellulose derivative. In such a composition, the effect of combining the cellulose derivative and the vinyl alcohol-based dispersant can be suitably exerted.

[0017] The total content of the cellulose derivative and the vinyl alcohol-based dispersant can be, for example, 1.5 g or more and 20 g or less relative to 100 g of the abrasive grains. According to such a polishing composition, new defects caused to the polishing object due to the load generated by polishing can be suppressed, and the surface of the polishing object can be processed with high quality.

[0018] The surface protective agent may further include an oxyalkylene additive. In such a composition, the effect obtained by using the cellulose derivative and the vinyl alcohol dispersant in combination can be appropriately exerted, and a higher-quality surface can be achieved.

[0019] In one embodiment of the polishing composition disclosed herein, the oxyalkylene additive may include an oxyalkylene additive OA having a Mw of less than 5000. L By using oxyalkylene additives OA L , which can further reduce surface defects after grinding.

[0020] As the abrasive grains in the technology disclosed herein, silica grains can be preferably used. The present invention can be preferably implemented in the form of a polishing composition containing silica grains as abrasive grains.

[0021] The polishing composition disclosed herein can be used for polishing various polishing objects. Among them, it can be preferably used for polishing silicon wafers and other substrates. In particular, it is suitable as a polishing composition used for fine polishing of silicon wafers. DETAILED DESCRIPTION

[0022] The following describes suitable embodiments of the present invention. It should be noted that features other than those specifically mentioned in this specification and required for implementing the present invention can be grasped as conventional technical selections by those skilled in the art based on the prior art in the art. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the art.

[0023] <Abrasive Grains>

[0024] The material or physical property of the abrasive grains contained in the grinding composition disclosed herein is not particularly limited, and can be appropriately selected according to the purpose or mode of use of the grinding composition. Examples of abrasive grains include inorganic particles, organic particles, and organic-inorganic composite particles. Specific examples of inorganic particles include oxide particles such as silicon dioxide particles, aluminum oxide particles, cerium oxide particles, chromium oxide particles, titanium dioxide particles, zirconium oxide particles, magnesium oxide particles, manganese dioxide particles, zinc oxide particles, and iron oxide red (Bengala) particles; nitride particles such as silicon nitride particles and boron nitride particles; carbide particles such as silicon carbide particles and boron carbide particles; diamond particles; carbonates such as calcium carbonate or barium carbonate, etc. Specific examples of organic particles include polymethyl methacrylate (PMMA) particles or poly (meth) acrylic acid particles, polyacrylonitrile particles, etc. Such abrasive grains can be used alone or in combination of two or more. It should be noted that (meth) acrylic acid in this specification refers to acrylic acid and methacrylic acid. Likewise, in this specification, a (meth)acryloyl group includes an acryloyl group and a methacryloyl group.

[0025] As the above-mentioned abrasive grains, inorganic grains are preferred, among which particles composed of metal or semimetal oxides are preferred, and silica grains are particularly preferred. In the grinding of grinding objects having a surface composed of silicon, such as silicon wafers described later, for example, in grinding compositions that can be used for fine grinding, it is particularly meaningful to use silica grains as abrasive grains. The technology disclosed herein can be preferably implemented in a manner such as that the above-mentioned abrasive grains are substantially composed of silica grains. Here, "substantially" means that more than 95% by weight, preferably more than 98% by weight, and more preferably more than 99% by weight of the particles constituting the abrasive grains are silica grains, and includes the meaning that 100% by weight are silica grains.

[0026] As specific examples of silica particles, colloidal silica, fumed silica, precipitated silica, etc. can be cited. The silica particles can be used alone or in combination of two or more. From the perspective of being able to easily obtain a polished surface with excellent surface quality after grinding, colloidal silica is particularly preferably used. As colloidal silica, colloidal silica made from water glass (Na silicate) as a raw material by an ion exchange method, or alkoxide method colloidal silica can be preferably used. Alkoxide method colloidal silica refers to colloidal silica manufactured by a hydrolysis condensation reaction of alkoxysilane. Colloidal silica can be used alone or in combination of two or more.

[0027] The true specific gravity (true density) of the abrasive material is preferably greater than 1.5, more preferably greater than 1.6, and further preferably greater than 1.7. Herein, the true specific gravity of the abrasive material refers to the true specific gravity of silicon dioxide constituting the silicon dioxide particles in the abrasive particles, for example, which are composed of silicon dioxide particles. It is also referred to as the true specific gravity of the abrasive particles hereinafter. By increasing the true specific gravity of the abrasive particles, the physical grinding ability of the abrasive particles tends to increase. The upper limit of the true specific gravity of the abrasive particles is not particularly limited, and is typically less than 2.3, for example, less than 2.2. As the true specific gravity of the abrasive particles, a measured value obtained by a liquid substitution method using ethanol as a substitution liquid can be used. The above-mentioned abrasive particles can be, for example, silicon dioxide particles.

[0028] The BET diameter of the abrasive is not particularly limited, but from the viewpoint of polishing efficiency, it is preferably 5 nm or more, and more preferably 10 nm or more. From the viewpoint of achieving a higher polishing effect, for example, from the viewpoint of further exerting the effect of reducing haze or removing defects, the above-mentioned BET diameter is, for example, preferably 15 nm or more, more preferably 20 nm or more, and may also exceed 20 nm. In addition, from the viewpoint of suppressing the local pressure imposed by the abrasive on the surface of the polishing object, the BET diameter of the abrasive is preferably 100 nm or less, more preferably 50 nm or less, and further preferably 40 nm or less. The technology disclosed herein can be implemented in a manner using abrasives having a BET diameter of 35 nm or less, preferably less than 35 nm, more preferably less than 32 nm, for example less than 30 nm, from the viewpoint of making it easier to obtain a higher-quality surface, such as a surface with a small LPD-N number and a low haze degree. The above-mentioned abrasive can be, for example, silica particles.

[0029] It should be noted that the BET diameter in this specification refers to the specific surface area (BET value) measured by the BET method, and is calculated according to BET diameter [nm] = 6000 / (true density [g / cm 3 ]×BET value [m 2 For example, in the case of silica particles, the particle size can be calculated by BET diameter [nm] = 2727 / BET value [nm 2 The specific surface area can be measured by using, for example, a surface area measuring device manufactured by Micromelitex, trade name "Flow Sorb II 2300".

[0030] The shape (outer shape) of the abrasive grains may be spherical or non-spherical. Specific examples of non-spherical grains include peanut-shaped, cocoon-shaped, candy-shaped, and rugby-shaped grains. The peanut-shaped grains are the shape of the shell of a peanut. For example, abrasive grains having a peanut-shaped or cocoon-shaped grains are preferably used.

[0031] The average aspect ratio of the abrasive grains, i.e., the average value of the major diameter / minor diameter ratio of the abrasive grains, is not particularly limited, but is theoretically 1.0 or more, preferably 1.05 or more, and more preferably 1.1 or more. By increasing the average aspect ratio, a higher grinding efficiency can be achieved. In addition, the average aspect ratio of the abrasive grains is preferably 3.0 or less, more preferably 2.0 or less, and more preferably 1.5 or less from the viewpoint of reducing scratches, etc.

[0032] The shape (outer shape) or average aspect ratio of the abrasive can be grasped, for example, by electron microscope observation. As a specific operation procedure for grasping the average aspect ratio, for example, a scanning electron microscope (SEM) can be used to draw the smallest rectangle circumscribed to the individual particle images for a specified number of silica particles whose shapes can be identified as independent particles. The above-mentioned specified number refers to, for example, 200. Moreover, for the rectangle drawn for each particle image, the length of its long side is set to the value of the long diameter, and the length of the short side is set to the value of the short diameter, and the value obtained by dividing the value of the long diameter by the value of the short diameter is calculated as the long diameter / short diameter ratio of each abrasive, that is, the aspect ratio. The average aspect ratio can be calculated by arithmetically averaging the aspect ratios of the above-mentioned specified number of particles.

[0033] <Surface Protectant>

[0034] The polishing composition disclosed herein contains a cellulose derivative and a vinyl alcohol-based dispersant as a surface protective agent. The surface protective agent can be configured so that the dispersibility parameter α described below is less than 100.

[0035] (Dispersion parameter α)

[0036] The dispersibility parameter α of the surface protective agent is as follows: the filtration time (liquid flow time) T of 100 g of a standard solution containing a standard polymer and ammonia and the remainder being water in a suction filtration performed in a prescribed manner. 0 , and the filtration time (liquid flow time) T of 100 g of the test liquid containing the surface protective agent and ammonia and the rest consisting of water 1 , calculated by the following formula.

[0037] Dispersion parameter α[%] = (T 1 / T 0 )×100

[0038] Here, the ammonia concentration of the standard solution and the test solution was set to 0.1 wt %. As the standard polymer, a polymer having a weight average molecular weight (Mw) of 25×10 4 The concentration of the standard polymer in the standard solution was set to 0.17 wt %. The concentration of the surface protective agent in the test solution was set so that the concentration of the cellulose derivative contained in the surface protective agent was 0.17 wt %.

[0039] The above-mentioned liquid flow time T 0 and T 1 The measurement is performed by the following operation.

[0040] [Filtration conditions]

[0041] Use filter:

[0042] Type: Membrane filter (φ47mm, disc type)

[0043] Material Nylon

[0044] Pore ​​size 0.2 μm

[0045] Suction pressure: 0.005MPa

[0046] [Measurement steps of liquid flow time]

[0047] The membrane filter is placed on the suction filter, and 100 g of deionized water is filtered under the above suction pressure, and then 100 g of the standard solution is filtered. At this time, the time required to filter 100 g of the standard solution (liquid flow time) is measured. 0 .

[0048] Next, the membrane filter was replaced with a new one, and 100 g of deionized water was filtered under the above suction pressure, and then 100 g of the test solution was filtered. At this time, the time required to filter 100 g of the test solution (liquid flow time) T was measured. 1 .

[0049] The α thus obtained can serve as an index for estimating the degree of dispersibility of the cellulose derivative in the polishing composition containing the surface protective agent. When a surface protective agent having an α of less than 100% is used, the cellulose derivative contained in the surface protective agent can be appropriately dispersed in the polishing composition, and defects caused by aggregation that may be contained in the cellulose derivative can be highly suppressed. In some embodiments, α may be less than 99%, for example, less than 98%. When a surface protective agent having an α of less than 96% is used, a higher effect can be exerted. The technology disclosed herein can still be appropriately implemented in a mode in which α is less than 90%, or less than 85%, for example, less than 80%. The lower limit of α is not particularly limited, for example, it can be more than 10%. From the perspective of further utilizing the protective effect obtained by the cellulose derivative or the effect of improving the surface wettability, α is generally more than 30%, more than 50%, more than 60%, or more than 70%, for example. α can be adjusted by selecting the type or molecular weight of the constituent components of the surface protective agent, setting their usage ratio, etc.

[0050] (Cellulose derivatives)

[0051] Cellulose derivatives are polymers containing β-glucose units as main repeating units. Specific examples of cellulose derivatives include hydroxyethyl cellulose (HEC), hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, carboxymethyl cellulose, etc. Among them, CHE is preferred.

[0052] The Mw of the cellulose derivative used in the polishing composition disclosed herein is not particularly limited, and may be, for example, 2×10 4 From the viewpoint of suitably exerting the functions of protection and surface wettability, the Mw of the cellulose derivative is usually appropriately 5×10 4 Above, can be 7×10 4 Above, can be 10×10 4 Above, can be 15×10 4 Above, it can also be, for example, 20×10 4 In addition, the Mw of the cellulose derivative can be set to, for example, 100×10 4 From the viewpoint of improving dispersibility, 70×10 4 Below, more preferably 50×10 4 In one embodiment, it is preferred to use a Mw of less than 50×10 4 , more preferably less than 30×10 4 , for example 28×10 4 The following cellulose derivatives.

[0053] In this specification, as the weight average molecular weight (Mw) of the water-soluble organic matter that can be contained in the polishing composition, a value based on gel permeation chromatography (GPC) (aqueous system, polyethylene oxide equivalent) can be adopted.

[0054] The proportion of cellulose derivatives in the surface protective agent is not particularly limited, and may be, for example, 20% by weight or more. The above proportion may be, for example, 20% by weight or more and less than 100% by weight. From the perspective of further utilizing the effect of the use of cellulose derivatives, the above proportion is usually appropriately 30% by weight or more, and may also be 50% by weight or more. The technology disclosed herein can be appropriately implemented in a manner in which the proportion of cellulose derivatives in the surface protective agent exceeds 50% by weight. The proportion of the above cellulose derivatives may be 60% by weight or more, 70% by weight or more, or 80% or more. In addition, from the perspective of utilizing the effect of the use of vinyl alcohol-based dispersants, the proportion of cellulose derivatives in the surface protective agent is usually appropriately made to be 99.9% by weight or less, may be 99.5% by weight or less, may be 99% by weight or less, or may be 98.5% by weight or less. In one embodiment, the proportion of cellulose derivatives in the surface protective agent may be 95% by weight or less, or may be 90% by weight or less.

[0055] The content of the cellulose derivative in the polishing composition is not particularly limited, and the content of the abrasive per 100 g of the polishing composition can be, for example, 0.1 g or more, or 0.5 g or more. From the viewpoint of further utilizing the effect of the cellulose derivative, the above content is usually appropriately set to 1 g or more, preferably 2 g or more. In one embodiment, the above content can be 3 g or more, or 4 g or more. In this embodiment, the significance of using the present invention can be further well exerted. In addition, from the viewpoint of the filterability or washability of the polishing composition, the content of the cellulose derivative per 100 g of the abrasive is usually appropriately set to 15 g or less, can be 12 g or less, can be 10 g or less, can be 8 g or less, or can be, for example, 6 g or less.

[0056] (Vinyl alcohol dispersant)

[0057] The surface protective agent disclosed herein includes a vinyl alcohol dispersant. Hereinafter, the vinyl alcohol dispersant is sometimes referred to as "dispersant VA". By using a cellulose derivative and a dispersant VA in combination, the dispersibility of the cellulose derivative in the polishing composition can be improved, and defects (e.g., LPD-N) caused by using the cellulose derivative can be effectively reduced.

[0058] As the dispersant VA, a water-soluble organic substance (typically a water-soluble polymer) containing a vinyl alcohol unit as its repeating unit is used. Here, the vinyl alcohol unit (hereinafter also referred to as "VA unit") is represented by the following chemical formula: -CH 2 -CH(OH)-; The VA unit can be produced by hydrolyzing (also referred to as saponifying) a repeating unit of a structure obtained by vinyl polymerization of a vinyl ester monomer such as vinyl acetate.

[0059] The dispersant VA may contain only VA units as repeating units, or may contain VA units and repeating units other than VA units (hereinafter also referred to as "non-VA units"). In the embodiment in which the dispersant VA contains non-VA units, the non-VA units may be repeating units having at least one structure selected from oxyalkylene groups, carboxyl groups, sulfonic groups, amino groups, hydroxyl groups, amide groups, imide groups, nitrile groups, ether groups, ester groups, and salts thereof. The dispersant VA may be a random copolymer containing VA units and non-VA units, or may be a block copolymer or a graft copolymer. The dispersant VA may contain only one non-VA unit, or may contain two or more non-VA units.

[0060] The ratio of the molar number of VA units to the molar number of all repeating units constituting the dispersant VA may be, for example, 5% or more, 10% or more, 20% or more, or 30% or more. There is no particular limitation, but in some embodiments, the ratio of the molar number of the above-mentioned VA units may be 50% or more, 65% or more, 75% or more, 80% or more, 90% or more, or, for example, 95% or more or 98% or more. The repeating units constituting the dispersant VA may be substantially 100% VA units. Here, "substantially 100%" means that at least the dispersant VA is not intentionally made to contain non-VA units. In other certain embodiments, the ratio of the molar number of VA units to the molar number of all repeating units constituting the dispersant VA may be, for example, less than 95%, less than 90%, less than 80%, or less than 70%.

[0061] The content of VA units in the dispersant VA can be, for example, 5% by weight or more, 10% by weight or more, 20% by weight or more, or 30% by weight or more on a weight basis. There is no particular limitation. In certain embodiments, the content of the VA units can be 50% by weight or more, 70% by weight or more, 80% by weight or more, 90% by weight or more, 95% by weight or more, or 98% by weight or more. Substantially 100% by weight of the repeating units constituting the dispersant VA can be VA units. Here, "substantially 100% by weight" means that at least the repeating units constituting the dispersant VA are not intentionally made to contain non-VA units. In certain other embodiments, the content of VA units in the dispersant VA can be, for example, less than 95% by weight, less than 90% by weight, less than 80% by weight, or less than 70% by weight.

[0062] Dispersant VA may include multiple polymer chains with different contents of VA units in the same molecule. Here, polymer chain refers to a part (chain segment) that constitutes a part of a molecule of polymer. For example, dispersant VA may include polymer chain A with a VA unit content higher than 50% by weight and polymer chain B with a VA unit content lower than 50% by weight in the same molecule. Polymer chain B with a VA unit content lower than 50% by weight means that the polymer chain B has a non-VA unit content higher than 50% by weight.

[0063] The polymer chain A may contain only VA units as repeating units, or may contain VA units and non-VA units. The content of VA units in the polymer chain A may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In certain embodiments, the content of VA units in the polymer chain A may be 95% by weight or more, or 98% by weight or more. Substantially 100% by weight of the repeating units constituting the polymer chain A may be VA units.

[0064] The polymer chain B may contain only non-VA units as repeating units, or may contain non-VA units and VA units. The content of non-VA units in the polymer chain B may be 60% by weight or more, 70% by weight or more, 80% by weight or more, or 90% by weight or more. In certain embodiments, the content of non-VA units in the polymer chain B may be 95% by weight or more, or 98% by weight or more. Substantially 100% by weight of the repeating units constituting the polymer chain B may be non-VA units.

[0065] Examples of dispersants VA containing polymer chains A and B in the same molecule include block copolymers or graft copolymers containing these polymer chains. The graft copolymers may be graft copolymers having a structure in which polymer chains B (side chains) are grafted onto polymer chains A (main chain), or graft copolymers having a structure in which polymer chains A (side chains) are grafted onto polymer chains B (main chain). In one embodiment, dispersants VA having a structure in which polymer chains B are grafted onto polymer chains A may be used.

[0066] Examples of polymer chain B include polymer chains having repeating units derived from N-vinyl monomers as main repeating units and polymer chains having repeating units derived from N-(meth)acryloyl monomers as main repeating units. It should be noted that, in this specification, the main repeating unit refers to a repeating unit containing more than 50% by weight unless otherwise specified.

[0067] As a suitable example of polymer chain B, there can be cited a polymer chain using N-vinyl monomers as main repeating units, i.e., an N-vinyl polymer chain. The content of repeating units derived from N-vinyl monomers in the N-vinyl polymer chain is typically more than 50% by weight, may be more than 70% by weight, may be more than 85% by weight, or may be more than 95% by weight. The polymer chain B may be substantially entirely composed of repeating units derived from N-vinyl monomers.

[0068] Examples of N-vinyl monomers include monomers having nitrogen-containing heterocyclic rings and N-vinyl chain amides. The above-mentioned heterocyclic ring may be, for example, a lactam ring. As specific examples of N-vinyl lactam monomers, N-vinyl pyrrolidone, N-vinyl piperidone, N-vinyl morpholine, N-vinyl caprolactam, N-vinyl-1,3-oxazine-2-one, N-vinyl-3,5-morpholinedione, etc. may be cited. As specific examples of N-vinyl chain amides, N-vinyl acetamide, N-vinyl propionamide, N-vinyl butyric acid amide, etc. may be cited. For example, more than 50% by weight of the repeating units of polymer chain B, such as 70% by weight or more, 85% by weight or more, or 95% by weight or more, may be N-vinyl polymer chains belonging to N-vinyl pyrrolidone units. Substantially all of the repeating units constituting polymer chain B may be N-vinyl pyrrolidone units.

[0069] As another example of polymer chain B, there can be mentioned a polymer chain having a repeating unit derived from an N-(meth)acryloyl type monomer as a main repeating unit, that is, an N-(meth)acryloyl polymer chain. The content of the repeating unit derived from the N-(meth)acryloyl type monomer in the N-(meth)acryloyl polymer chain is typically more than 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. Substantially all of polymer chain B may be repeating units derived from N-(meth)acryloyl type monomers.

[0070] Examples of N-(meth)acryloyl monomers include chain amides having N-(meth)acryloyl groups and cyclic amides having N-(meth)acryloyl groups. Examples of chain amides having N-(meth)acryloyl groups include (meth)acrylamide; N-alkyl (meth)acrylamide such as N-methyl (meth)acrylamide, N-ethyl (meth)acrylamide, N-propyl (meth)acrylamide, N-isopropyl (meth)acrylamide, and N-n-butyl (meth)acrylamide; and N,N-dimethyl (meth)acrylamide, N,N-diethyl (meth)acrylamide, N,N-dipropyl (meth)acrylamide, N,N-diisopropyl (meth)acrylamide, and N,N-di(n-butyl) (meth)acrylamide. Examples of the cyclic amide having an N-(meth)acryloyl group include N-(meth)acryloylmorpholine and N-(meth)acryloylpyrrolidine.

[0071] As another example of polymer chain B, there can be mentioned a polymer chain containing an oxyalkylene unit as a main repeating unit, that is, an oxyalkylene polymer chain. The content of the oxyalkylene unit in the oxyalkylene polymer chain is typically more than 50% by weight, and may be 70% by weight or more, 85% by weight or more, or 95% by weight or more. Substantially all the repeating units contained in polymer chain B may be oxyalkylene units.

[0072] Examples of oxyalkylene units include oxyethylene units, oxypropylene units, oxybutylene units, etc. Such oxyalkylene units may be repeating units derived from corresponding alkylene oxides. The oxyalkylene units contained in the oxyalkylene chain segments may be a single type or may be two or more types. For example, it may be an oxyalkylene chain segment comprising a combination of oxyethylene units and oxypropylene units. In the oxyalkylene polymer chain comprising two or more oxyalkylene units, their oxyalkylene units may be random copolymers of alkylene oxides of the corresponding alkylene oxides, or may be block copolymers or graft copolymers.

[0073] The weight average molecular weight (Mw) of the dispersant VA is not particularly limited, and may be, for example, 2000 or more, and may be greater than 5000. From the viewpoint of being able to easily and appropriately exert the dispersibility improvement effect, the Mw of the dispersant VA may be 7000 or more, and may be 1×10 4 Above, it can be 1.2×10 4 In one embodiment, a Mw of 2×10 4 Above, for example 3×10 4 Above or 5×10 4 Above or 7×10 4 The above dispersant VA. In addition, the Mw of the dispersant VA is usually appropriately 100×104 Below, for example, 50×10 4 Below, can be 30×10 4 Below, also 20×10 4 From the viewpoint of obtaining a higher dispersibility improvement effect, in one embodiment, a Mw of 17×10 4 Below, for example 15×10 4 The following dispersants are VA.

[0074] The relationship between the surface protective agent disclosed herein and the Mw of the cellulose derivative is not particularly limited, and can preferably be implemented in a mode containing a dispersant VA with a lower Mw. According to this mode, there is a tendency to make it easier to appropriately exert the advantages obtained by using a cellulose derivative. In one mode, the Mw of the dispersant VA can be set to less than 90% of the Mw of the cellulose derivative, that is, it can be set to less than 0.9 times. The Mw of the dispersant VA can be set to less than 75% of the Mw of the cellulose derivative, can be set to less than 60%, and can also be set to, for example, less than 50%. In addition, the Mw of the dispersant VA is generally appropriately set to more than 0.5% of the Mw of the cellulose derivative, preferably more than 1%. From the viewpoint of making it easy to appropriately exert the dispersibility improvement effect, in some modes, the Mw of the dispersant VA can be set to more than 2% of the Mw of the cellulose derivative, can be set to more than 3%, can be set to more than 5%, can be set to more than 10%, can be set to more than 20%, and can also be set to more than 30%.

[0075] The proportion of the dispersant VA in the surface protective agent is not particularly limited and can be set in a manner to obtain the desired dispersibility improvement effect. In one embodiment, the proportion of the dispersant VA in the surface protective agent can be set to, for example, 0.05% by weight or more, usually appropriately set to 0.1% by weight or more, and from the perspective of obtaining a higher dispersibility improvement effect, it can be set to 0.5% by weight or more, can be set to 1% by weight or more, and can also be set to 1.5% by weight or more. In addition, the proportion of the dispersant VA in the surface protective agent can be set to, for example, 50% by weight or less, and from the perspective of easily and appropriately exerting the effect of the use of the cellulose derivative, it can be set to 30% by weight or less, can be set to 20% by weight or less, can be set to 15% by weight or less, can be set to 10% by weight or less, and can also be set to, for example, 7% by weight or less. The technology disclosed herein can still be appropriately implemented in a manner in which the proportion of the dispersant VA in the surface protective agent is 5% by weight or less, for example, 4% by weight or less.

[0076] The content of the dispersant VA per 100 g of the cellulose derivative is not particularly limited, and can be, for example, 0.1 g or more, 0.2 g or more, 0.5 g or more, 1 g or more, 1.5 g or more, or 2 g or more. As the content of the dispersant VA increases, it tends to be easier to achieve a higher dispersibility improvement effect. In addition, the content of the dispersant VA per 100 g of the cellulose derivative can be, for example, 80 g or less, and from the perspective of further improving the use effect of the cellulose derivative, it is usually appropriately set to 50 g or less, preferably 30 g or less, 20 g or less, 15 g or less, 10 g or less, 7 g or less, or, for example, 5 g or less.

[0077] The content of the dispersant VA in the grinding composition is not particularly limited. For example, the abrasive grains in the grinding composition can be set to more than 0.0001g, more than 0.0005g, more than 0.001g, more than 0.005g, more than 0.01g, more than 0.02g, more than 0.05g, or more than 0.07g. As the content of the dispersant VA increases, it is easy to obtain a higher dispersibility improvement effect. In some embodiments, the content of the dispersant VA in the grinding composition can be, for example, more than 0.1g, more than 0.2g, more than 1.2g, or more than 2.5g. In addition, the content of the dispersant VA per 100g of abrasive grains is usually appropriately set to less than 10g from the viewpoint of cleaning or economy, and can also be set to less than 5g. In certain embodiments, the content of the dispersant VA in the polishing composition may be, for example, 3 g or less, 2 g or less, 1 g or less, or 0.5 g or less.

[0078] The total content of the cellulose derivative and the dispersant VA in the polishing composition is not particularly limited. For example, the content of the abrasive in the polishing composition can be set to 1.1 g or more per 100 g of the abrasive, and is usually appropriately set to 1.5 g or more, can be set to 2 g or more, can be set to 2.5 g or more, can be set to 3 g or more, can be set to 3.5 g or more, and can also be set to 4 g or more. As the above total content increases, it tends to be easier to achieve a higher dispersibility improvement effect. In some embodiments, the above total content can be 7 g or more, or 10 g or more. In addition, the total content of the cellulose derivative and the dispersant VA per 100 g of the abrasive is usually appropriately set to 30 g or less, preferably 20 g or less, and can also be set to 15 g or less from the perspective of cleaning or economy. In some embodiments, the above total content can be set to 12 g or less, or can also be set to 10 g or less. The technology disclosed herein can still be appropriately implemented in a mode in which the total content of the cellulose derivative and the dispersant VA per 100 g of the abrasive is 8 g or less (for example, 6 g or less).

[0079] (Oxyalkylene additives)

[0080] The surface protective agent in the technology disclosed herein may also contain an oxyalkylene additive as needed. As the oxyalkylene additive, a water-soluble organic substance containing more than 50% by weight of an oxyalkylene unit structure can be used appropriately. As the oxyalkylene additive, one such water-soluble organic substance can be used alone, or two or more can be used in combination. A nonionic water-soluble organic substance is preferred. Hereinafter, the oxyalkylene additive is sometimes referred to as "additive OA".

[0081] As water-soluble organic substances that can be used as additives OA, for example, block copolymers of polyethylene oxide (PEO), ethylene oxide (EO) and propylene oxide (PO) or butylene oxide (BO), random copolymers of EO and PO or BO, etc. can be cited. Among them, block copolymers of EO and PO or random copolymers of EO and PO are preferred. Block copolymers of EO and PO can be diblock copolymers, triblock copolymers, etc. containing PEO blocks and polypropylene oxide (PPO) blocks. Examples of the above-mentioned triblock copolymers include PEO-PPO-PEO type triblock copolymers and PPO-PEO-PPO type triblock copolymers. PEO-PPO-PEO type triblock copolymers are usually more preferred. In the block copolymer or random copolymer of EO and PO, the molar ratio of EO and PO constituting the copolymer (EO / PO) is preferably greater than 1, more preferably more than 2, further preferably more than 3, and can also be, for example, more than 5 from the perspective of solubility in water or cleaning properties.

[0082] Other examples of water-soluble organic substances that can be used as additive OA include oxyalkylene polymers such as polyethylene glycol, polypropylene glycol, and polybutylene glycol; polyoxyethylene alkyl ethers, polyoxyethylene alkylphenyl ethers, polyoxyethylene alkylamines, polyoxyethylene fatty acid esters, polyoxyethylene glyceryl ether fatty acid esters, polyoxyethylene sorbitan fatty acid esters, and other polyoxyalkylene derivatives, such as polyoxyalkylene adducts. Suitable examples include polyethylene glycol and polyoxyethylene alkyl ethers. Polyoxyethylene alkyl ethers may be, for example, polyoxyethylene decyl ether.

[0083] Specific examples of the polyoxyalkylene derivatives include polyoxyethylene propyl ether, polyoxyethylene butyl ether, polyoxyethylene pentyl ether, polyoxyethylene hexyl ether, polyoxyethylene octyl ether, polyoxyethylene-2-ethylhexyl ether, polyoxyethylene nonyl ether, polyoxyethylene decyl ether, polyoxyethylene isodecyl ether, polyoxyethylene tridecyl ether, polyoxyethylene lauryl ether, polyoxyethylene cetyl ether, polyoxyethylene stearyl ether, polyoxyethylene isostearyl ether, polyoxyethylene oleyl ether, polyoxyethylene phenyl ether, polyoxyethylene octylphenyl ether, polyoxyethylene nonylphenyl ether, polyoxyethylene dodecyl ether, polyoxyethylene octylphenyl ... Phenyl ether, polyoxyethylene styrenated phenyl ether, polyoxyethylene lauryl amine, polyoxyethylene stearamide, polyoxyethylene oleamide, polyoxyethylene monolaurate, polyoxyethylene monostearate, polyoxyethylene distearate, polyoxyethylene monooleate, polyoxyethylene dioleate, polyoxyethylene sorbitan monolaurate, polyoxyethylene sorbitan monopalmitate, polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan trioleate, polyoxyethylene sorbitan tetraoleate, polyoxyethylene castor oil, polyoxyethylene hydrogenated castor oil, etc.

[0084] The weight average molecular weight (Mw) of the additive OA is not particularly limited, but is usually appropriately set to 10×10 4 Below, for example, 5×10 4 Below, can be 3×10 4 Below, can be 2×10 4 Below, can be 1×10 4 Below, it may be below 9500, and may be, for example, below 9000. In addition, the Mw of the additive OA is generally appropriately above 200, preferably above 250, for example, above 300, from the viewpoint of improving the surface grade after grinding. The more preferred range of the Mw of the additive OA may also vary depending on the type of the additive OA. For example, when a polyoxyethylene alkyl ether or an oxyalkylene polymer (such as polyethylene glycol) is used as the additive OA, its Mw is preferably below 5000, and may also be below 2500, for example, below 1000. In addition, when a triblock copolymer of, for example, a PEO-PPO-PEO type is used as the additive OA, its Mw may be, for example, above 1000, may be above 3000, or may be above 5000.

[0085] The proportion of the additive OA in the surface protective agent is not particularly limited. The above proportion can be, for example, 0.05% by weight or more, or 0.5% by weight or more. From the perspective of achieving a higher use effect, it can be 1% by weight or more, or 5% by weight or more. In addition, from the perspective of easily and appropriately exerting the use effect of the cellulose derivative, the proportion of the additive OA in the surface protective agent is usually appropriately set to 30% by weight or less, and can be set to 25% by weight or less, can be set to 20% by weight or less, or can be set to 15% by weight or less.

[0086] The content of the additive OA per 100 g of the cellulose derivative is not particularly limited, and may be, for example, 0.1 g or more, 1 g or more, or 3 g or more. In addition, from the viewpoint of easily and appropriately exerting the use effect of the cellulose derivative, the content of the additive OA per 100 g of the cellulose derivative is usually appropriately set to 100 g or less, and may be set to 70 g or less, may be set to 50 g or less, may be set to 30 g or less, may be set to 20 g or less, or may be set to 15 g or less.

[0087] The content of the additive OA in the polishing composition is not particularly limited, and can be, for example, 0.0001 g or more, 0.01 g or more, or 0.05 g or more per 100 g of abrasive grains in the polishing composition. In addition, the content of the additive OA per 100 g of abrasive grains is usually appropriately set to 5 g or less, can be set to 3 g or less, or can be set to 1 g or less.

[0088] The content of the additive OA per 1 g of the dispersant VA is not particularly limited, and can be, for example, 0.01 g or more, 0.1 g or more, or 0.3 g or more. In addition, the content of the additive OA per 1 g of the dispersant VA is usually appropriately set to 20 g or less, 15 g or less, 10 g or less, 5 g or less, or 1 g or less.

[0089] In one embodiment of the technology disclosed herein, the surface protective agent can be combined with a dispersant VA and an oxyalkylene additive (additive OA) having a weight average molecular weight (Mw) of less than 5000. L ). By using the additive OA L , which can further reduce the surface defects after grinding, such as LPD-N number. As an additive OA L Among the above materials exemplified as water-soluble organic substances that can be used as additive OA, those having a Mw of less than 5000 can be used. Additive OA L The Mw of the OA may be 2500 or less, 1000 or less, or, for example, 800 or less. In addition, from the viewpoint of appropriately exerting the surface defect reduction effect, the additive OA LThe Mw of the additive OA is preferably 200 or more, and may be 250 or more, or, for example, 300 or more. In one embodiment, an additive OA having a Mw of 350 or more may be used. L。 It is preferred to use OA as an additive L Non-limiting examples of materials can include oxyalkylene polymers and polyoxyethylene alkyl ethers. The oxyalkylene polymers can be, for example, polyethylene glycol. The polyoxyethylene alkyl ethers can be, for example, polyoxyethylene decyl ether.

[0090] Dispersant VA per 1g of additive OA L The content of is not particularly limited, and can be, for example, 0.01 g or more, 0.05 g or more, 0.1 g or more, or 0.3 g or more. In addition, the content of the additive OA per 1 g of the dispersant VA is usually appropriately set to 10 g or less, 5 g or less, 3 g or less, 2 g or less, 1 g or less, or, for example, 0.7 g or less.

[0091] <Basic Compounds>

[0092] The basic compound can be suitably selected from various basic compounds having the function of being dissolved in water and raising the pH of the aqueous solution. For example, nitrogen-containing organic or inorganic basic compounds, hydroxides of alkali metals, hydroxides of alkaline earth metals, various carbonates or bicarbonates, etc. can be used. Examples of nitrogen-containing basic compounds include quaternary ammonium compounds, quaternary phosphonium compounds, ammonia, amines, etc. As the above-mentioned amine, water-soluble amines are preferred. Such basic compounds can be used alone or in combination of two or more.

[0093] As specific examples of alkali metal hydroxides, potassium hydroxide, sodium hydroxide, etc. can be cited. As specific examples of carbonates or bicarbonates, ammonium bicarbonate, ammonium carbonate, potassium bicarbonate, potassium carbonate, sodium bicarbonate, sodium carbonate, etc. can be cited. As specific examples of amines, methylamine, dimethylamine, trimethylamine, ethylamine, diethylamine, triethylamine, ethylenediamine, monoethanolamine, N-(β-aminoethyl)ethanolamine, hexamethylenediamine, diethylenetriamine, triethylenetetramine, anhydrous piperazine, piperazine hexahydrate, 1-(2-aminoethyl)piperazine, N-methylpiperazine, guanidine, imidazole or triazole and other azoles can be cited. As specific examples of quaternary phosphonium compounds, quaternary phosphonium hydroxides such as tetramethylphosphonium hydroxide and tetraethylphosphonium hydroxide can be cited.

[0094] As the quaternary ammonium compound, a quaternary ammonium salt such as a tetraalkylammonium salt or a hydroxyalkyltrialkylammonium salt can be preferably used. The anion component in the quaternary ammonium salt can be, for example, OH - 、F - , Cl - Br - ,I - , ClO 4- , BH 4 - As the quaternary ammonium salt, a strong base is preferred. As a preferred example, the anion is OH - The quaternary ammonium salt is a quaternary ammonium hydroxide. Specific examples of quaternary ammonium hydroxides include tetraalkylammonium hydroxides such as tetramethylammonium hydroxide, tetraethylammonium hydroxide, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, tetrapentylammonium hydroxide, and tetrahexylammonium hydroxide; and hydroxyalkyltrialkylammonium hydroxides such as 2-hydroxyethyltrimethylammonium hydroxide (also called choline). Among them, tetraalkylammonium hydroxides are preferred, and tetramethylammonium hydroxide (TMAH) is preferred.

[0095] As the basic compound in the technology disclosed herein, at least one basic compound selected from alkali metal hydroxides, quaternary ammonium hydroxides and ammonia is preferred. Among them, quaternary ammonium hydroxides such as tetramethylammonium hydroxide and ammonia are preferred, and ammonia is particularly preferred.

[0096] <Water>

[0097] The polishing composition disclosed herein typically contains water. As water, ion exchange water (deionized water), pure water, ultrapure water, distilled water, etc. can be preferably used. Since the water used should avoid hindering the effects of other components contained in the polishing composition as much as possible, the total content of transition metal ions is preferably 100 ppb or less. For example, the purity of water can be improved by removing impurity ions generated by ion exchange resins, removing foreign matter generated by filters, distillation, etc.

[0098] <Other ingredients>

[0099] The polishing composition disclosed herein may further contain known additives that can be used in polishing compositions, such as chelating agents, organic acids, organic acid salts, inorganic acids, inorganic acid salts, preservatives, and mildew inhibitors, as needed, within the range that does not significantly hinder the effects of the present invention. The polishing composition disclosed herein can be suitably implemented in a mode that substantially does not contain a chelating agent. The above-mentioned additives can be, for example, known additives that can be used in polishing compositions used in the polishing process of silicon wafers.

[0100] The polishing composition disclosed herein preferably does not substantially contain an oxidant. This is because, if the polishing composition contains an oxidant, when, for example, a silicon substrate such as a silicon wafer is polished as the polishing object, the polishing composition is supplied to the polishing object, and the surface of the polishing object is oxidized to form an oxide film, thereby reducing the polishing efficiency. As a specific example of the so-called oxidant herein, hydrogen peroxide (H 2 O 2), sodium persulfate, ammonium persulfate, sodium dichloroisocyanurate, etc. It should be noted that the polishing composition does not substantially contain an oxidizing agent means that the oxidizing agent is at least intentionally not contained.

[0101] The polishing composition disclosed herein may also contain a water-soluble polymer (hereinafter, also referred to as an arbitrary polymer) other than a cellulose derivative and a dispersant VA as an arbitrary component within the range that does not significantly hinder the effect of the present invention. As such an arbitrary polymer, for example, starch derivatives, N-vinyl polymers, N-(meth)acryloyl polymers, etc. can be used. Examples of starch derivatives include α-starch, pullulan, carboxymethyl starch, cyclodextrin, etc. The N-vinyl polymer may be a homopolymer or copolymer of the N-vinyl monomer exemplified above with respect to polymer chain B. As specific examples of N-vinyl polymers, homopolymers of N-vinyl pyrrolidone (VP), or copolymers in which the copolymerization ratio of VP is 70% by weight or more, etc. may be cited. The N-(meth)acryloyl polymer may be a homopolymer or copolymer of the N-(meth)acryloyl monomer exemplified above with respect to polymer chain B. As specific examples of N-(meth)acryloyl-type polymers, homopolymers of N-isopropylacrylamide (NIPAM), copolymers in which the copolymerization ratio of NIPAM is 70% by weight or more, homopolymers of N-acryloylmorpholine (ACMO), copolymers in which the copolymerization ratio of ACMO is 70% by weight or more, etc. can be cited. The arbitrary polymer is preferably nonionic. The content of the arbitrary polymer is appropriately set to 30g or less per 100g of cellulose derivative, preferably set to 10g or less, and can also be set to 5g or less, or can also be 1g or less. The technology disclosed herein can be suitably implemented in a manner that substantially does not contain such an arbitrary polymer.

[0102] <ph>

[0103] The pH of the polishing composition disclosed herein is usually appropriately 8.0 or more, preferably 8.5 or more, more preferably 9.0 or more, further preferably 9.5 or more, for example 10.0 or more. When the pH of the polishing composition becomes higher, there is a tendency to improve the polishing efficiency. On the other hand, from the viewpoint of preventing the dissolution of abrasive particles such as silica particles and suppressing the reduction of the mechanical polishing effect caused by the abrasive particles, the pH of the polishing composition is appropriately 12.0 or less, preferably 11.8 or less, more preferably 11.5 or less, and further preferably 11.0 or less.

[0104] In the technology disclosed herein, the pH of a liquid composition is determined by placing a glass electrode in the composition to be measured after a three-point calibration using a standard buffer using a pH meter, and measuring the value after 2 minutes or more of stabilization. The standard buffer is a phthalate pH buffer pH: 4.01 (25°C), a neutral phosphate pH buffer pH: 6.86 (25°C), and a carbonate pH buffer pH: 10.01 (25°C). As a pH meter, for example, a glass electrode hydrogen ion concentration indicator manufactured by Horiba, Ltd., Model F-23, or an equivalent thereof can be used.

[0105] <Purpose>

[0106] The polishing composition disclosed in the technology can be applied to polishing objects of various materials and shapes. The material of the polishing object can be, for example, metals or semi-metals such as silicon, aluminum, nickel, tungsten, copper, tantalum, titanium, stainless steel, or their alloys; glassy substances such as quartz glass, aluminosilicate glass, and glassy carbon; ceramic materials such as aluminum oxide, silicon dioxide, sapphire, silicon nitride, tantalum nitride, and titanium carbide; compound semiconductor substrate materials such as silicon carbide, gallium nitride, and gallium arsenide; resin materials such as polyimide resin, etc. The polishing object can also be composed of multiple materials among these.

[0107] The polishing composition disclosed in the art is particularly preferably used for polishing a surface made of silicon, such as a silicon wafer. A typical example of the silicon wafer is a silicon single crystal wafer obtained by slicing a silicon single crystal ingot.

[0108] The polishing composition disclosed herein can be preferably used in a polishing process of an object to be polished, such as a polishing process of a silicon wafer. Before the polishing process using the polishing composition disclosed herein, the object to be polished can also be subjected to general treatment of the object to be polished in a process upstream of the polishing process, such as grinding or etching.

[0109] The polishing composition disclosed herein can be preferably used for polishing of a polishing object, such as a silicon wafer, which is prepared into a surface state with a surface roughness of 0.01nm to 100nm through an upstream process. The surface roughness Ra of the polishing object can be measured using, for example, a laser scanning surface roughness meter "TMS-3000WRC" manufactured by Schmitt Measurement System Inc. It is effective for use in final polishing (fine polishing) or polishing before it, and is particularly preferably used for final polishing. Here, final polishing refers to the last polishing step in the manufacturing process of the target object, that is, a step in which no further polishing will be performed after this step.

[0110] <Polishing Composition>

[0111] The polishing composition disclosed herein is typically supplied to the polishing object in the form of a polishing liquid containing the polishing composition, and is used for polishing the polishing object. The above-mentioned polishing liquid can be, for example, prepared by diluting any of the polishing compositions disclosed herein. The dilution of the polishing composition can typically be carried out by water. Or, the polishing composition can also be used directly as a polishing liquid. That is, the concept of the polishing composition in the technology disclosed herein includes: a polishing liquid (also called working slurry) supplied to the polishing object and used to polish the polishing object; and, a concentrated liquid diluted and used as a polishing liquid. The above-mentioned concentrated liquid can also be grasped as a stock solution of the polishing liquid. As another example of a polishing liquid containing the polishing composition disclosed herein, a polishing liquid formed by adjusting the pH of the composition can be cited.

[0112] (Grinding fluid)

[0113] The content of the abrasive grains in the polishing liquid is not particularly limited, and is typically 0.01% by weight or more, preferably 0.05% by weight or more, more preferably 0.10% by weight or more, for example 0.13% by weight or more. With the increase in the content of the abrasive grains, a higher polishing rate can be achieved. From the viewpoint of achieving a relatively low haze surface, the above content is usually appropriately 10% by weight or less, preferably 7% by weight or less, more preferably 5% by weight or less, further preferably 2% by weight or less, for example 1% by weight or less, 0.5% by weight or less, or 0.3% by weight or less.

[0114] The concentration of the surface protective agent in the polishing liquid is not particularly limited, and can be set to, for example, 0.0005% by weight or more. From the viewpoint of obtaining a higher protective effect, the preferred concentration is 0.001% by weight or more, and more preferably 0.002% by weight or more. In some embodiments, the concentration of the surface protective agent can be, for example, 0.003% by weight or more, or 0.005% by weight or more. In addition, the concentration of the surface protective agent can be, for example, 1.0% by weight or less, usually appropriately 0.5% by weight or less, can be 0.1% by weight or less, can be 0.05% by weight or less, or can be, for example, 0.02% by weight or less.

[0115] The concentration of the cellulose derivative in the polishing liquid is not particularly limited, and can be, for example, 0.0001% by weight or more. From the viewpoint of reducing haze, the concentration is preferably 0.0005% by weight or more, more preferably 0.001% by weight or more, for example 0.003% by weight or more, or 0.005% by weight or more. In addition, from the viewpoint of polishing efficiency, the concentration of the cellulose derivative is usually preferably 0.2% by weight or less, more preferably 0.1% by weight, or 0.05% by weight or less, or, for example, 0.01% by weight or less.

[0116] The concentration of the dispersant VA in the polishing liquid is not particularly limited, and can be set to, for example, 0.00001% by weight or more, and from the viewpoint of obtaining a higher dispersibility improvement effect, can be set to 0.00005% by weight or more, and can also be set to 0.0001% by weight or more. In some embodiments, the concentration of the dispersant VA can be 0.0005% by weight or more, and can also be 0.001% by weight or more. In addition, from the viewpoint of polishing efficiency, the concentration of the dispersant VA is usually preferably set to 0.1% by weight or less, can be set to 0.01% by weight or less, can be set to 0.005% by weight or less, can be set to 0.001% by weight or less, and can also be set to, for example, 0.0005% by weight or less.

[0117] When the polishing composition disclosed herein includes a basic compound, the concentration of the basic compound in the polishing liquid is not particularly limited. From the viewpoint of improving the polishing speed, it is usually preferred to set the above concentration to 0.0005% by weight or more of the polishing liquid, and more preferably to 0.001% by weight or more. In addition, from the viewpoint of reducing the haze, the above concentration is appropriately set to less than 0.3% by weight, preferably less than 0.1% by weight, and more preferably less than 0.05% by weight (e.g., 0.03% by weight).

[0118] (Concentrate)

[0119] The polishing composition disclosed herein may also be in a concentrated form before being supplied to the polishing object. The above-mentioned concentrated form refers to a concentrated solution of the polishing liquid, and can also be grasped as a stock solution of the polishing liquid. From the perspective of convenience or cost reduction during manufacturing, circulation, storage, etc., such a concentrated polishing composition is more advantageous. The concentration ratio is not particularly limited, for example, it can be set to about 2 to 100 times in volume conversion, usually about 5 to 50 times, and can be, for example, about 10 to 40 times.

[0120] Such a concentrated liquid can be diluted at a desired timing to prepare a polishing liquid (working slurry), and the polishing liquid can be supplied to the polishing object for use. The dilution is performed by, for example, adding water to the concentrated liquid and mixing.

[0121] The content of the abrasive in the concentrate can be, for example, 50% by weight or less. From the viewpoint of the operability of the concentrate, for example, the dispersion stability or filterability of the abrasive, the content of the abrasive in the concentrate is usually preferably 45% by weight or less, and can also be 40% by weight or less, for example, 30% by weight or less. In addition, from the viewpoint of convenience in production, distribution, storage, etc. or cost reduction, the content of the abrasive can be, for example, 0.5% by weight or more, preferably 1% by weight or more, can be 2% by weight or more, and can also be 3% by weight or more.

[0122] (Preparation of Polishing Composition)

[0123] The polishing composition used in the technology disclosed herein may be a single-dose form or a multi-dose form represented by a two-dose form. For example, it may be composed by mixing a portion A containing at least abrasive grains among the constituent components of the polishing composition with a portion B containing at least a portion of the remaining components, and mixing and diluting them at an appropriate time as needed to prepare a polishing liquid.

[0124] The preparation method of the grinding composition is not particularly limited. For example, known mixing devices such as a paddle stirrer, an ultrasonic disperser, and a homogenizing mixer can be used to mix the components constituting the grinding composition. The manner of mixing these components is not particularly limited, and for example, all the components can be mixed at once or in a suitably set step.

[0125] <Grinding>

[0126] The polishing composition disclosed herein is used for polishing an object to be polished, for example, in an embodiment including the following operations. A preferred embodiment of a method for polishing an object to be polished, for example, a silicon wafer, using the polishing composition disclosed herein is described below.

[0127] That is, a polishing liquid containing any of the polishing compositions disclosed herein is prepared. The polishing liquid can be prepared by performing concentration adjustment such as dilution or pH adjustment on the polishing composition. Alternatively, the polishing composition can be directly used as a polishing liquid.

[0128] Next, the polishing liquid is supplied to the polishing object, and polishing is performed by conventional methods. For example, when fine polishing a silicon wafer, the silicon wafer that has undergone a grinding process is typically mounted on a general polishing device, and the polishing liquid is supplied to the polishing surface of the silicon wafer through the polishing pad of the polishing device. Typically, the polishing liquid is continuously supplied, and the polishing pad is pressed against the polishing surface of the silicon wafer, and the two are moved relative to each other, such as rotating. The polishing of the polishing object is completed after this polishing process.

[0129] The polishing pad used in the above-mentioned polishing step is not particularly limited, and for example, a foamed polyurethane type, a nonwoven type, a suede type, etc. polishing pad can be used. Each polishing pad may contain abrasive grains or may not contain abrasive grains. It is usually preferred to use a polishing pad that does not contain abrasive grains.

[0130] The polishing object polished by the polishing composition disclosed herein is typically cleaned. Cleaning can be performed using an appropriate cleaning solution. The cleaning solution used is not particularly limited. For example, in the field of semiconductors, general SC-1 cleaning solution, SC-2 cleaning solution, etc. can be used. The SC-1 cleaning solution is ammonium hydroxide (NH 4 OH) and hydrogen peroxide (H 2 O 2 ) and water (H 2 The SC-2 cleaning solution is a mixture of HCl and H 2 O 2 With H 2 The temperature of the cleaning solution can be set to, for example, a range of about 90°C or higher than room temperature. The room temperature is typically about 15°C to 25°C. From the viewpoint of improving the cleaning effect, a cleaning solution of about 50°C to 85°C can be preferably used.

[0131] Example

[0132] Several embodiments of the present invention are described below, but the present invention is not intended to be limited to the contents shown in these embodiments. It should be noted that in the following description, "%" is a weight basis except when it represents the numerical value of the dispersion parameter.

[0133] <Preparation of Polishing Composition>

[0134] (Example 1)

[0135] The following polishing composition was prepared: colloidal silica with a BET diameter of 25 nm at a concentration of 0.175%, a PEO-PPO-PEO block copolymer with a Mw of 9000 at a concentration of 0.00125%, ammonia at a concentration of 0.005%, and a polyvinyl alcohol with a Mw of 25×10 4 Hydroxyethyl cellulose (HEC) with a concentration of 0.0003% and polyvinyl alcohol (PVA, saponification degree of 95% or more) with a Mw of 13,000.

[0136] (Example 2)

[0137] In Example 1, PVA having a Mw of 106,000 was used instead of PVA having a Mw of 13,000. Except for this, the polishing composition of this example was prepared in the same manner as in Example 1.

[0138] (Example 3)

[0139] In Example 1, a graft copolymer having a Mw of 175,000 and having a saponification degree of 95% or more polyvinyl alcohol (PVA) as the main chain and polyvinyl pyrrolidone (PVP) as the side chain (hereinafter referred to as "PVA-g-PVP") was used instead of PVA. Other than this, the polishing composition of this example was prepared in the same manner as in Example 1.

[0140] (Example 4)

[0141] In Example 1, the concentration of PVA was changed to 0.0002%. In addition, polyethylene glycol (PEG) having a Mw of 600 was further contained at a concentration of 0.0001%. Except for this, the polishing composition of this example was prepared in the same manner as in Example 1.

[0142] (Example 5)

[0143] The following polishing composition was prepared: colloidal silica with a BET diameter of 25 nm at a concentration of 0.088%, polyoxyethylene decyl ether with a Mw of 400 at a concentration of 0.0006%, ammonia at a concentration of 0.006%, and a polyoxyethylene decyl ether with a Mw of 25×10- 4 HEC of 0.004% and polyvinyl alcohol (PVA, saponification degree of 95% or more) with a Mw of 106,000.

[0144] (Comparative Example 1)

[0145] A polishing composition of this example was prepared in the same manner as in Example 1 except that PVA was not used.

[0146] (Comparative Example 2)

[0147] In Example 1, polyvinyl pyrrolidone (PVP) having a Mw of 45,000 was used instead of PVA. Except for this, the same operation as in Example 1 was carried out to prepare a polishing composition of this example.

[0148] (Comparative Examples 3 and 4)

[0149] The polishing composition of this example was prepared in the same manner as in Examples 1 and 2 except that HEC was not used.

[0150] The dispersion parameters α of the polishing compositions of these examples and comparative examples were measured by the above-mentioned method. As the test liquid of Examples 1 to 3 and Comparative Examples 1 and 2, the following test liquid was used: the surface protective material of the polishing composition of each example was contained in a concentration of 0.17% of HEC constituting the surface protective material, and 0.1% of ammonia was also contained, and the remainder was composed of water. Specifically, the following test liquid was used in Examples 1 and 2: it contained 0.17% HEC, 0.006% PVA with a Mw of 13000 or 106000, 0.025% PEO-PPO-PEO, 0.1% ammonia, and the remainder was composed of water. The following test liquid was used in Example 3: it contained 0.17% HEC, 0.006% PVA-g-PVP, 0.025% PEO-PPO-PEO, 0.1% ammonia, and the remainder was composed of water. In Example 4, the following test solution was used: HEC 0.17%, PVA 0.004%, PEG 0.002%, PEO-PPO-PEO 0.025%, ammonia 0.1%, and the remainder was water. In Example 5, the following test solution was used: HEC 0.17%, PVA 0.091%, C10PEO 0.014%, ammonia 0.1%, and the remainder was water. In Comparative Example 1, the following test solution was used: HEC 0.17%, PEO-PPO-PEO 0.025%, ammonia 0.1%, and the remainder was water. In Comparative Example 2, the following test solution was used: HEC 0.17%, PEO-PPO-PEO 0.025%, PVP 0.006%, ammonia 0.1%, and the remainder was water. The results are shown in Table 1. It should be noted that, regarding Comparative Examples 3 and 4 not containing HEC, the test liquid having the composition of HEC removed from the test liquids used in the measurement of the dispersion parameter α of the polishing composition of Examples 1 and 2, that is, the measured values ​​of the test liquid containing 0.006% PVA having a Mw of 13,000 or 106,000, 0.025% PEO-PPO-PEO, 0.1% ammonia, and the remainder consisting of water are recorded in parentheses as reference values.

[0151] <Silicon Wafer Grinding>

[0152] (1) Pre-grinding process

[0153] A primary polishing composition containing 0.95% abrasive and 0.065% alkaline compound with the remainder being water was prepared. Colloidal silica with a BET diameter of 35 nm was used as an abrasive. Potassium hydroxide (KOH) was used as an alkaline compound. The primary polishing composition was directly used as a polishing liquid (working slurry), and a silicon wafer as a polishing object was masked under the following polishing condition 1. The silicon wafer used was a commercially available silicon single crystal wafer with a diameter of 200 mm (conductivity type: P type, crystal orientation: <100> , resistivity: above 1Ω·cm and below 100Ω·cm, no COP).

[0154] [Grinding Condition 1]

[0155] Grinding device: Blade grinder manufactured by Okamoto Machine Tool Co., Ltd., model "PNX-322"

[0156] Grinding load: 15kPa

[0157] Plate speed: 30rpm

[0158] Carrier speed: 30rpm

[0159] Polishing pad: Made by Fujibo Ehime Co., Ltd., product name "FP55"

[0160] Grinding liquid supply rate: 0.55 liters / minute

[0161] Grinding fluid temperature: 20°C

[0162] Plate cooling water temperature: 20℃

[0163] Grinding time: 3 minutes

[0164] (2) Fine grinding process

[0165] The polishing compositions of the above-mentioned Examples and Comparative Examples were used directly as polishing liquids (working slurries), respectively, and the silicon wafers that had completed the above-mentioned preliminary polishing step were polished under the following polishing conditions 2.

[0166] [Grinding Condition 2]

[0167] Grinding device: Blade grinder manufactured by Okamoto Machine Tool Co., Ltd., model "PNX-322"

[0168] Grinding load: 15kPa

[0169] Plate speed: 30rpm

[0170] Carrier speed: 30rpm

[0171] Polishing Pad: A polishing pad manufactured by Fuji Boshoku Ehime Co., Ltd., trade name "POLYPAS27NX"

[0172] Polishing Liquid Supply Rate: 0.4 L / min

[0173] Temperature of the Polishing Liquid: 20°C

[0174] Temperature of the Flat Plate Cooling Water: 20°C

[0175] Polishing Time: 4 minutes

[0176] Take out the polished silicon wafer from the polishing apparatus and use NH 4 OH (29%): H 2 O 2 (31%): Deionized water (DIW) = 1:1:15 (volume ratio) cleaning solution for cleaning (SC-1 cleaning). More specifically, prepare 2 cleaning tanks, respectively contain the above cleaning solution in these first and second cleaning tanks, keep at 60°C, immerse the polished silicon wafer in the first cleaning tank for 15 minutes, then through a rinsing tank using ultrapure water and ultrasonic waves, immerse in the second cleaning tank for 15 minutes, and then dry it using a spin dryer.

[0177] <LPD-N Number Measurement>

[0178] Use a wafer inspection apparatus manufactured by KLA-Tencor Corporation, trade name "SURFSCAN SP2", and measure the number of LPD-N present on the surface (polished surface) of the silicon wafers obtained from the above respective examples in the DCO mode of this apparatus. Convert the LPD-N numbers for each example into relative values with the LPD-N number of Comparative Example 1 set as 100%, and based on this conversion value, use the following 6 levels to evaluate the LPD-N numbers. The results are shown in Table 1.

[0179] A: Less than 40%

[0180] B: 40% or more and less than 50%

[0181] C: 50% or more and less than 60%

[0182] D: 60% or more and less than 100%

[0183] E: 100% or more and less than 150%

[0184] F: 150% or more

[0185] [Table 1]

[0186] Table 1

[0187]

[0188] As shown in Table 1, the polishing compositions of Examples 1 to 5, which comprised a cellulose derivative and a vinyl alcohol-based dispersant and contained a surface protective agent S1 having a dispersibility parameter α of less than 100, were found to have significantly lower LPD-N numbers after fine polishing than the polishing composition of Comparative Example 1. On the other hand, the polishing composition of Comparative Example 2, in which α exceeded 100, could not achieve an effect of lowering the LPD-N number. In addition, in Comparative Examples 3 and 4, in which the cellulose derivative was removed from the polishing compositions of Examples 1 and 2, the surface quality after fine polishing was significantly lowered.

[0189] Although specific examples of the present invention have been described in detail above, these are merely examples and do not limit the claims of the patent. The technology described in the scope of protection of the patent application includes various modifications and changes to the specific examples described above.< / ph>

Claims

1. A polishing composition comprising abrasive grains, a basic compound and a surface protective agent, wherein: The surface protective agent comprises a cellulose derivative and a vinyl alcohol-based dispersant, The dispersibility parameter α of the surface protective agent is less than 100, The weight average molecular weight of the cellulose derivative is 5×10 4 Above and below 30×10 4 , The weight average molecular weight of the vinyl alcohol dispersant is 2000 or more and 15×10 4 the following, The content of the abrasive grains in the polishing composition is 0.01 wt % or more and 10 wt % or less, The concentration of the cellulose derivative in the polishing composition is 0.0001 wt % or more and 0.2 wt % or less, The concentration of the vinyl alcohol-based dispersant in the polishing composition is 0.00001 wt % or more and 0.1 wt % or less, The concentration of the basic compound in the polishing composition is 0.0005 wt % or more and less than 0.3 wt %.

2. The polishing composition according to claim 1, wherein The weight average molecular weight of the vinyl alcohol-based dispersant is 20% to 90% of the weight average molecular weight of the cellulose derivative.

3. The polishing composition according to claim 1 or 2, wherein The surface protective agent has a dispersibility parameter α of 90 or less.

4. The polishing composition according to claim 1 or 2, wherein The content of the vinyl alcohol-based dispersant is 0.1 g or more and 80 g or less based on 100 g of the cellulose derivative.

5. The polishing composition according to claim 1 or 2, wherein The total content of the cellulose derivative and the vinyl alcohol-based dispersant is 1.5 g or more and 20 g or less relative to 100 g of the abrasive.

6. The polishing composition according to claim 1 or 2, wherein The surface protective agent further includes an oxyalkylene additive.

7. The polishing composition according to claim 6, comprising an oxyalkylene additive OA having a weight average molecular weight of less than 5000 L As the oxyalkylene additive.

8. The polishing composition according to claim 1 or 2, wherein The abrasive particles are silicon dioxide particles. 9 . The polishing composition according to claim 1 , which is used for polishing a silicon wafer.

Citation Information

Patent Citations

  • Wetting agent for semiconductor, and composition for polishing and polishing method using the same

    JP2012089862A

  • Wetting agent for semiconductor substrate and composition for polishing

    JP2015124231A